Political Aspirations and Perils of Security Unpacking the Military Strategy of the United Nations - Edström, H.; Gyllensporre, D.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
This book comprises of a range of case studies of military strategy, based on UN documents, observing and concluding the effectiveness of each individual case. Edstrom and Gyllensporre analyse the UN's military strategy, its consequences and its potential to fulfil political ambitions.
Keywords: Politics and war; International relations; Peace; International organization; Diplomacy; Political science; Military and Defence Studies; International Relations; Conflict Studies; International Organization; Diplomacy; Political Science